2015
DOI: 10.1111/vcp.12288
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Lactate Scout point‐of‐care instrument for the determination of blood l‐lactate concentration in sheep

Abstract: The Lactate Scout has high accuracy and precision, with a negligible bias. It is a reliable POC analyzer to assess L-lactate concentration in ovine medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Results of the present study did not confirm findings from previous studies validating the Lactate Scout (previous model to the Lactate Scout+). The device used in the earlier validation studies was an older model (Lactate Scout, SensLab GmbH, Leipzig, Germany) that was validated in pigs [17], horses [14], dogs [25], sheep [16], and cattle [18,20]. The Lactate Scout+ is a newer model than the Lactate Scout, and its novel features include a compensatory mechanism for differences in hematocrit and integrated Bluetooth technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the present study did not confirm findings from previous studies validating the Lactate Scout (previous model to the Lactate Scout+). The device used in the earlier validation studies was an older model (Lactate Scout, SensLab GmbH, Leipzig, Germany) that was validated in pigs [17], horses [14], dogs [25], sheep [16], and cattle [18,20]. The Lactate Scout+ is a newer model than the Lactate Scout, and its novel features include a compensatory mechanism for differences in hematocrit and integrated Bluetooth technology.…”
Section: Discussionmentioning
confidence: 99%
“…L-lactate can be measured using methodologies, such as commercially available enzymatic analytical assays, blood gas analyzers, or hand-held devices, with the latter ones being developed to be more time and cost effective than traditional analytical methods. Lactate Scout hand-held monitors have been validated for use in horses [14], dogs [15], sheep [16], pigs [17], cows, and calves [18]. Hand-held analyzers, such as the Accusport (Boheringer, Mannheim, Germany), Accutrend Plus (Roche Diagnostics, Mannheim, Germany), i-STAT (Abbott Point of Care, Abbott Laboratories, Chicago, IL), Lactate Scout (SensLab GmbH, Leipzig, Germany), and Lactate Pro (Arkay Inc, Kyoto, Japan) were shown to correlate (r > 0.94) with the laboratory based measures in cattle with different diseases [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The unit proves to be a reliable lactate measurement system with an inter-rater reliability with a correlation coefficient of r = 0.95 for inter-rater reliability and r = 0.91 for intra-rater reliability (Tanner et al 2010 ). The Lactate Scout is reported to have 99% accuracy and 98% precision (Kaynar et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover the portable analyzers could be more practical to use during some critical interventions [11,12]. The latest studies showed the introduction of the lactate pocket analyzer in ovine medicine [13].…”
mentioning
confidence: 99%